Dual functional hydrogel of osteoclastic-inhibition and osteogenic-stimulation for osteoporotic bone defect regeneration - Lei Yu; Wentao Wang; Chang Lv; Qian Chen; Peng Yang; Zhenrong Qi; Haomiao Yu; Ruiqi Cao; Wenhao Li; Yi Qin; Gaoran Ge; Peilai Liu; et al. (Materials Today Bio, 2025)
Osteoporotic bone regeneration poses significant challenges due to the complexity of the condition. Osteoporosis, a degenerative disorder, results from an imbalance in bone homeostasis driven by dysregulation of osteoblast and osteoclast activity. This complicates the treatment of osteoporosis and its related bone injuries in clinical practice. Despite the development of various polymer scaffolds for bone defect repair, achieving effective regeneration in osteoporotic bones—especially when combined with osteoporosis medications—remains difficult. In this study, we designed a drug delivery system composed of mesoporous bioactive glass (MBG) and photo-crosslinked hyaluronic acid methacrylate (HAMA). This system, loaded with the osteogenesis-promoting peptide DWIVA (D5) and the osteoclastogenesis-inhibiting drug alendronate (ALN), is gelled using a light initiator and 405 nm wavelength light. The MBG@D5-Gel complex enables the controlled spatiotemporal release of these agents, markedly enhancing bone regeneration in osteoporotic conditions within ovariectomized rats by inhibiting osteoclastogenesis and bone resorption while promoting osteogenic differentiation and mineralization. This dual-action system synergistically regulates osteoblast and osteoclast activity, optimizing the pathological microenvironment of osteoporosis and facilitating the repair of osteoporotic bone defects. MBG@D5-Gel holds great potential as an effective organic-inorganic hybrid biomimetic implant material for the treatment of osteoporotic bone defects.